The role of digital literacy in achieving health equity in the third millennium society: A literature review - Campanozzi, Laura Leondina; Gibelli, Filippo; Bailo, Paolo; Nittari, Giulio; Sirignano, Ascanio; Ricci, Giovanna (Frontiers in Public Health, 2023)
Healthcare in the third millennium is largely delivered through systems involving the use of the technological devices and services, foremost among them telemedicine. For the adequate delivery of digital medicine services, however, it is necessary for users to be digitally literate, that is, able to consciously make use of technology. In order to understand how relevant digital literacy is in determining the effectiveness of e-Health services, we performed a traditional literature review on 3 major databases by combining the terms “Digital Literacy” and “Computer Literacy” with the terms “Telemedicine” and “Telehealth”. Starting from an initial library of 1077 papers, we selected 38 articles. At the outcome of the search, we found that digital literacy is a pivotal element in conditioning the effectiveness of telemedicine and digital medicine services in general, however, with some limitations.